The control of effective source rocks on the distribution of hydrocarbon reservoirs in a lacustrine rift-basin: insights from a 3D basin modeling study - Bang Zeng; Jianhua Qu; Zhongrong Mi; En Xie; Hui Fu; Sibo Yang; Yang Shi; Meijun Li (Journal of Petroleum Exploration and Production Technology)
Abstract This study addresses the challenge of understanding hydrocarbon reservoir distribution in lacustrine rift-basins, particularly in the Fushan Depression of the South China Sea, where intricate tectonic and sedimentary dynamics complicate analysis. Effective source kitchens play a critical role in controlling hydrocarbon accumulation patterns, yet existing studies often rely on statistical methods limited by exploration biases. To overcome these shortcomings, 3D basin modeling was employed to assess the influence of effective source rocks on the distribution of hydrocarbons. The findings reveal that reservoirs in lacustrine rift-basins are closely linked to effective source rocks, exhibiting lateral migration patterns that form rings around the source kitchen, as well as vertical migration patterns concentrated above the effective source rock centers. Hydrocarbon migration is generally short-range, extending laterally up to 12 km and vertically up to 2 km. Notably, oil and gas pools are predominantly located in sedimentary facies transition zones, with key resources concentrated within a 3–6 km radius of the source rock in the lower petroleum system and at depths of 3–4 km in the upper system. This work quantitatively assesses the role of effective source rocks, offering crucial insights for future exploration in similar basins. The novelty lies in its comprehensive modeling approach, which enhances understanding of hydrocarbon distribution beyond prior statistical frameworks, providing a robust foundation for exploration and development strategies.